SISTEM OPTIK INTERFEROMETER MICHELSON MENGGUNAKAN DUA SUMBER LASER UNTUK MEMPEROLEH POLA FRINJI - Yayuk Widamarti; Minarni '; Maksi Ginting (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Wavemeter could be built using an interferometer with two laser sources. In this  study, Michelson interferometer was built using two lasers which  were  He-Ne  laser and diode laser. Characteristics  of its fringe pattern were  analyzed based on  the laser power and beam size. The results showed that fringe pattern for laser He-Ne was  obtained at  arm length  12.5 cm x 12.5 cm with the  beam  height  from   optical  table of  11.7 cm. He-Ne laser used was  632.8 nm  in  wavelength    with the 5 mW  power  made by  Meredith instrument. The  diode laser  had wavelength  650 nm with the power  of  5 mW  made byRoithner. The output of He-Ne laser from the  interferometer system  had 0.3 mW, diode laser by  0.5 mW. The best  fringe pattern for both lasers was with visibilities  rangedfrom  0.63 and 0.098, and beam width of each laser  of 4.11 mm  for He-Ne laser and 4.30 mm x 4.26 mm for diode laser.